2015
DOI: 10.1177/0891988715601735
|View full text |Cite
|
Sign up to set email alerts
|

Citalopram for the Treatment of Agitation in Alzheimer Dementia

Abstract: Objective To assess potential genetic influences on citalopram treatment efficacy for agitation in individuals with Alzheimer dementia (AD). Six functional genetic variants were studied in the following genes: serotonin receptor 2A (HTR2A-T102C), serotonin receptor 2C (HTR2C-Cys23Ser), serotonin transporter (5HTT-LPR), brain-derived neurotropic factor (BDNF-Val66-Met), apolipoprotein E (ε2, ε3, ε4 variants), and cytochrome P450 (CYP2C19). Treatment response by genotype was measured by (1) the agitation domain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…A significant association between 5-HTT promoter region (5-HTTPR) polymorphism and aggression was found in two studies , and between 5-HTT variable number tandem repeat (VNTR) polymorphism and aggression in another study (Ueki et al, 2007). These relationships, however, were not confirmed in several other studies (Assal et al, 2004;Ha et al, 2005;Peters et al, 2016;Pritchard et al, 2008;Proitsi et al, 2012).…”
Section: Measurements Of Central 5-ht Activity In Humans Have Been Prmentioning
confidence: 92%
See 1 more Smart Citation
“…A significant association between 5-HTT promoter region (5-HTTPR) polymorphism and aggression was found in two studies , and between 5-HTT variable number tandem repeat (VNTR) polymorphism and aggression in another study (Ueki et al, 2007). These relationships, however, were not confirmed in several other studies (Assal et al, 2004;Ha et al, 2005;Peters et al, 2016;Pritchard et al, 2008;Proitsi et al, 2012).…”
Section: Measurements Of Central 5-ht Activity In Humans Have Been Prmentioning
confidence: 92%
“…Two studies found a significant association between the 5-HT2A T102C polymorphism and agitation (Assal et al, 2004;Peters et al, 2016), whilst several others, including two performed in populations of non-White ethnicity, did not support this relationship (Holmes et al, 1998;Lai et al, 2011;Lam et al, 2004;Pritchard et al, 2008;Proitsi et al, 2012). Similarly, more studies reported no significant association between 5-HT2C receptor polymorphisms and agitation (Holmes et al, 1998;Pritchard et al, 2008;Proitsi et al, 2012) than one that did (Peters et al, 2016). Genetic analysis of 5-HTT has also provided contradictory findings.…”
Section: Measurements Of Central 5-ht Activity In Humans Have Been Prmentioning
confidence: 99%
“…The CITAD trial randomized 186 people with AD to citalopram (ascending to 30 mg per day) or placebo for 9 weeks, demonstrating benefits in the primary outcome for agitation [83]. More recently, an analysis of secondary outcomes suggested benefits in both delusions and hallucinations in participants receiving citalopram compared with those receiving placebo, with the best response in individuals with psychosis and agitation [84].…”
Section: Citaloprammentioning
confidence: 99%
“…One study (Moretti et al, 2002) had multiple elements judged as having a high risk of bias; this was largely due to the fact that it was not doubleblinded. Three studies were judged to have low risk of bias across all elements: sertraline or mirtazapine for depression in dementia (HTA-SADD; Banerjee et al, 2013Banerjee et al, , 2011, Depression in Alzheimer's Disease Study -Phase II (DIADS-II) (Drye et al, 2011;Martin et al, 2006;Rosenberg et al, 2010;Weintraub et al, 2010) and Citalopram for Agitation in Alzheimer's Disease (CitAD; Peters et al, 2016;Porsteinsson et al, 2014; Table 3).…”
Section: Reviewmentioning
confidence: 99%
“…The best trial in this area is the large (n = 186) welldesigned CitAD trial (Peters et al, 2016;Porsteinsson et al, 2014). In this 9-week RCT comparing citalopram with placebo, all the participants had probable AD and clinically significant agitation.…”
Section: Antidepressants For Agitation In Dementiamentioning
confidence: 99%